Belin Belin - Marjeta Šašel Kos (Studia Mythologica Slavica, 2015)
As late as the end of the 19th century a tradition concerning Belin was still alive in the area of Tolmin, among the Slovenes there, who regarded Belin as a great healer and believed that with his »key« it was possible to cure blindness. It may be hypothesized that there was a continuity of worship of the Aquileian Belinus/Belenus, through the late Roman period and late antiquity up to the early Slavic period. The Slavs that settled in this region would have taken over from the indigenous folk the cult of the god and modified it consistent with their own beliefs. Perhaps they brought with them the cult of Belibog, Belin(ec), whereupon a mingling of the two divinities came about.